Career Adaptability Skills in Javanese Sandur Tradition for Generation Z Career Development - M. Khoirudin Jalil; M Ramli (PSDKU Guidance and Counseling, Universitas Negeri Surabaya, 2025)
The Javanese Sandur tradition offers a unique cultural context for developing career adaptability skills in Generation Z, yet its potential remains underexplored in existing career development research. This study employs a qualitative participatory ethnographic design over five months in Karang Village, Tuban Regency, East Java, involving participant observation, in-depth interviews with Sandur practitioners, and document analysis. Data were thematically analyzed using Maxqda with an inductive approach. The findings reveal that active engagement in Sandur cultivates four core adaptability dimensions—concern, control, curiosity, and confidence—through collective performance practices, role exploration, cultural responsibility, and problem-solving within the community. These results demonstrate that Sandur is not only a form of cultural preservation but also a strategic medium for strengthening career adaptability among Generation Z facing rapid technological and social transitions. This research contributes new insights into how traditional cultural practices can serve as contextualized pathways for enhancing career readiness in modern work environments.